2018
DOI: 10.3389/fmicb.2018.00314
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With High-Hydrostatic Pressure, Activated Film Packaging With Thymol Plus Enterocin AS-48, and Its Combination Modify the Bacterial Communities of Refrigerated Sea Bream (Sparus aurata) Fillets

Abstract: The aim of this study was to determine the impact of activated plastic films with thymol and enterocin AS-48 and high-hydrostatic pressure (HP) treatment on the bacterial load and bacterial diversity of vacuum-packaged sea bream fillets under refrigerated storage for 10 days. The activated film and the HP treatment reduced aerobic mesophiles viable counts by 1.46 and 2.36 log cycles, respectively, while the combined treatment achieved a reduction of 4.13 log cycles. HP and combined treatments resulted in longe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 53 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…Taking into consideration that bacteriocins are more effective against Gram-positive bacteria and possess a narrow antimicrobial spectrum, they are used in food packaging in combination with other antimicrobials or preservation techniques. Over the last five years, the use of enterocin AS-48 [47], bacteriocins-like substances [48] or bacteriocin-producing strains [49] with modified atmosphere packaging or high hydrostatic pressure has yielded improved results in the packaging of chilled food products. Furthermore, bacteriocin combination with other antimicrobials such as thymol [47,50], carvacrol [50], EDTA [51] or chitosan [17,52] have also improved their antibacterial action in food products such as meat and fish.…”
Section: Antimicrobial Substances Used In Food Packagingmentioning
confidence: 99%
“…Taking into consideration that bacteriocins are more effective against Gram-positive bacteria and possess a narrow antimicrobial spectrum, they are used in food packaging in combination with other antimicrobials or preservation techniques. Over the last five years, the use of enterocin AS-48 [47], bacteriocins-like substances [48] or bacteriocin-producing strains [49] with modified atmosphere packaging or high hydrostatic pressure has yielded improved results in the packaging of chilled food products. Furthermore, bacteriocin combination with other antimicrobials such as thymol [47,50], carvacrol [50], EDTA [51] or chitosan [17,52] have also improved their antibacterial action in food products such as meat and fish.…”
Section: Antimicrobial Substances Used In Food Packagingmentioning
confidence: 99%
“…Ortega Blázquez et al. (2018) reported that the combination of HPP (300 MPa/23 °C/5 min) and enterocin AS‐48 and thymol through active package reduced the total aerobic bacteria in sea bream fillets by 4.13 log cycles, while single treatment induced 2.36 or 1.46 log cycles, respectively. Pérez‐Baltar et al.…”
Section: Microbial Inactivation By Combination Of Hpp and Selected Humentioning
confidence: 99%
“…found that more than 5 log reduction of both L. innocua and E. coli in carrot juice was achieved by the combination of HPP (300 MPa/35 • C/2 min) and nisin (0.0025%, w/w), compared with less than 1 log reduction in the absence of nisin. OrtegaBlázquez et al (2018) reported that the combination of HPP (300 MPa/23 • C/5 min) and enterocin AS-48 and thymol through active package reduced the total aerobic bacteria in sea bream fillets by 4.13 log cycles, while single treatment induced 2.36 or 1.46 log cycles, respectively Pérez-Baltar et al (2019). reported that HPP (450 MPa/18…”
mentioning
confidence: 99%
“…In samples treated with the activated film, bacteria were reduced to 0.00% of all the microorganisms at day 0. After 10-day storage relative abundance of Listeria genus in the treated and untreated samples were of 0.09% and 0.79%, respectively [ 116 ].…”
Section: Food Model Systemsmentioning
confidence: 99%